Biotechnology of plasma proteins - Lundblad, Roger L. (Boca Raton : CRC Press, 2013)
"Discussing the role of plasma proteins in current biotechnology, this book describes the protein composition of human plasma, the fractionation of plasma to obtain therapeutic proteins, and the analysis of these products. It delineates the path from plasma products to recombinant products, and highlights products from albumin, intravenous immunoglobins, and coagulation. It offers a comprehensive review of current techniques for the analysis of proteins including electrophoresis, chromatography, spectrophotometry, and mass spectrometry as well as updates not published since 1975"--Provided by publisher.
Includes bibliographical references.
Description based on metadata supplied by the publisher and other sources.
Electronic reproduction. Santa Fe, Arg.: elibro, 2020. Available via World Wide Web. Access may be limited to eLibro affiliated libraries.
Keywords: Blood proteins -- Biotechnology; Electronic books